Oxygen-dependent inactivation of gramicidin S synthetase in Bacillus brevis. - Friebel, T E (1977)
Incorporation of L-[14C]ornithine into gramicidin S by crude, unfractionated lysozyme extracts of Bacillus brevis ATCC 9999 was shown to represent the activity of the gramicidin synthetase complex. Frozen-thawed cells were the source of active extracts, but when cells were shaken in air at 37 degrees C, they rapidly lost activity in a first-order reaction with a half-life of 13 min. Protease inhibitors and inhibitors of energy metabolism had no effect on the inactivation process in frozen-thawed cells. Stabilization was achieved when the cells were shaken in nitrogen or helium instead of air. The addition of dithiothreitol produced a moderate degree of stabilization. The L-ornithine- and D-phenylalanine-activating activities of the gramicidin S synthetase complex were also lost during aeration of the cells. Crude cell-free extracts also lost activity when they were shaken in oxygen, but, in this case, inactivation was slower (half-life of 80 min). Nitrogen also stabilized these cell-free extracts.